Application of Cerium Dioxide Nanoparticles and Chromium-Resistant Bacteria Reduced Chromium Toxicity in Sunflower Plants - Ma, Jing; Alshaya, Huda; Okla, Mohammad K.; Alwasel, Yasmeen A.; Chen, Fu; Adrees, Muhammad; Hussain, Afzal; Hameed, Salma; Shahid, Munazzam Jawad (Frontiers in Plant Science, 2022)
The continuous increase in the heavy metals concentration in the soil due to anthropogenic activities has become a global issue. The chromium, especially hexavalent chromium, is highly toxic for living organisms due to high mobility, solubility, and carcinogenic properties. Considering the beneficial role of nanoparticles and bacteria in alleviating the metal stress in plants, a study was carried out to evaluate the role of cerium dioxide (CeO2) nanoparticles (NPs) and Staphylococcus aureus in alleviating the chromium toxicity in sunflower plants. Sunflower plants grown in chromium (Cr) contaminated soil (0, 25, 50 mg kg-1) were treated with CeO2 nanoparticles (0, 25, 50 mg L-1) and S. aureus. The application of CeO2 NPs significantly improved plant growth and biomass production, reduced oxidative stress, and enhanced the enzymatic activities in the sunflower plant grown under chromium stress. The application of S. aureus further enhanced the beneficial role of nanoparticles in alleviating metal-induced toxicity. The maximum improvement was noted in plants treated with both nanoparticles and S. aureus. The augmented application of CeO2 NPs (50 mg L-1) at Cr 50 mg kg-1 increased the chl a contents from 1.2 to 2.0, chl b contents 0.5 to 0.8 and mg g-1 FW, and decreased the leakage of the electrolyte from 121 to 104 %. The findings proved that the application of CeO2 nanoparticles and S. aureus could significantly ameliorate the metal-induced stress in sunflower plants. The findings from this study can provide new horizons for research in the application of nanoparticles in phytoremediation and bioremediation. Keywords: Bacteria, Chromium, Nanoparticles, Phytoremediation, Sunflower.